Jurisprudential and Legal foundations and effects of Flagrant Offences - mehdi choopani (پژوهش‌نامه حقوق اسلامی, 2010)
one categorization, offences in criminal law are divided into flagrant and non flagrant ones. Procedural laws of Iran concerning flagrant offences have adopted quick legal procedures with the minimum formalities. Substantial laws have also dealt with aggravated punishment and particular criminalization concerning flagrant offences. This criminal institution has certain jurisprudential foundations. In the Shiite jurisprudence, flagrant offences are known by expressions such as overtly committing a sinful conduct, open commission of sins, or public commission of sins. Numerous regulations also affect one having committed these offences such as his failure to benefit from a share of Khums and Zakat, permission of disapproving and dishonoring him, extinction of his justice and invalidation of his testimony. In the criminal procedure approach, easy and quick action in dealing with these offences is taken into account. The essential characteristic of the jurisprudential approach is substantial focus on social responses to the offence, a fact being manifested in severe and serious social responses to the offence, and being deprived of certain social rights. However, the common point in the jurisprudential and legal literature is the provision of the institution of flagrant offences as an independent institution. In both jurisprudential and legal approaches, flagrant offences due to their open commission are recognized as an independent institution with unique characteristics.